2017
DOI: 10.1523/jneurosci.2561-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Nerve-Specific Input Modulation to Spinal Neurons during a Motor Task in the Monkey

Abstract: If not properly regulated, the large amount of reafferent sensory signals generated by our own movement could destabilize the CNS. We investigated how input from peripheral nerves to spinal cord is modulated during behavior. We chronically stimulated the deep radial nerve (DR; proprioceptive, wrist extensors), the median nerve (M; mixed, wrist flexors and palmar skin) and the superficial radial nerve (SR; cutaneous, hand dorsum) while four monkeys performed a delayed wrist flexion-extension task. Spinal neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
63
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 58 publications
5
63
2
Order By: Relevance
“…After excluding from further analysis two neurons that were classified as putative motoneurons, the total number of neurons analyzed was 142. This dataset overlaps with a previous paper (Confais, Kim, Tomatsu, Takei, & Seki, 2017) that focused on the differences between SR and DR neurons (i.e. responsiveness to nerve stimulation, central latency, base firing rate, and intra-spinal depth of each neuron).…”
Section: Resultsmentioning
confidence: 70%
See 4 more Smart Citations
“…After excluding from further analysis two neurons that were classified as putative motoneurons, the total number of neurons analyzed was 142. This dataset overlaps with a previous paper (Confais, Kim, Tomatsu, Takei, & Seki, 2017) that focused on the differences between SR and DR neurons (i.e. responsiveness to nerve stimulation, central latency, base firing rate, and intra-spinal depth of each neuron).…”
Section: Resultsmentioning
confidence: 70%
“…The median of the mean firing rate for five behavioral epochs clearly indicated that the DR and SR neurons increased their activity during active torque (active move and active hold) and passive movement for both flexion and extension movements. Their activity was significantly larger in extension trials (Wilcoxon signed rank test, active move, P = 0.001; active hold, P = 0.020; passive move, P = 0.043) (see also (Confais et al, 2017)). We further characterized this activity by separately counting the number of neurons showing significant modulation relative to rest (Figure 3C) in each behavioral epoch.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations